High-Order and High Accurate CFD Methods and Their Applications for Complex Grid Problems (Communications in Computational Physics, 2020)
The purpose of this article is to summarize our recent progress in high-orderand high accurate CFD methods for flow problems with complex grids as well asto discuss the engineering prospects in using these methods. Despite the rapid development of high-order algorithms in CFD, the applications of high-order and highaccurate methods on complex configurations are still limited. One of the main reasons which hinder the widely applications of these methods is the complexity of grids.Many aspects which can be neglected for low-order schemes must be treated carefullyfor high-order ones when the configurations are complex. In order to implement high-order finite difference schemes on complex multi-block grids, the geometric conservation law and block-interface conditions are discussed. A conservative metric method isapplied to calculate the grid derivatives, and a characteristic-based interface conditionis employed to fulfil high-order multi-block computing. The fifth-order WCNS-E-5proposed by Deng [9, 10] is applied to simulate flows with complex grids, includinga double-delta wing, a transonic airplane configuration, and a hypersonic X-38 configuration. The results in this paper and the references show pleasant prospects inengineering-oriented applications of high-order schemes.